Branding UMKM Untuk Meningkatkan Penjualan Pada UMKM Bawang Goreng Di Desa Ngepoh - Ria Mei Yustiana; Lia Nirawati (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Branding is a very important aspect for MSME players in starting a business because it can increase sales and attract customer interest. Currently, MSME branding in Indonesia has various conditions, some are still weak and some have good branding aspects in accordance with today's technological advances, so this causes many MSMEs to lack understanding of branding due to the lack of knowledge from MSME actors regarding information and digital marketing. To overcome these obstacles, branding is carried out such as making logos, packaging, product photos, creating social media accounts and e-commerce. The logo itself is very important for MSMEs because the goal is for their products to be known by the public with their own brand. Marketing through social media can reach a wider community. The purpose of MSME branding is to help market MSME products so that they can make products better known to the public and can reach a wider market. Therefore, MSMEs in Ngepoh Village can introduce these products and maximize their sales. The method used is qualitative through the implementation of surveys, interviews, and documentation of activities on MSME actors. The results of this MSME branding are that MSME products have developed and the marketing of their products is also going well.